2001
DOI: 10.1177/0022022101032001008
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Cognitive Style in Middle Eastern and Western Groups

Abstract: Integrative cognitive style among Middle Eastern immigrants to Canada and native-born Euro-Canadians was assessed by looking at their performance on a multidimensional classification task and an object sorting task. Results showed high levels of integrative thinking in Middle Eastern immigrants compared with Euro-Canadians. The contrasting differentiative cognitive style was avoided by the Middle Eastern group, whereas a higher level of differentiation was observed in the Euro-Canadian groups. These results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…In contrast, Americans' memory for focal objects was independent of the background (Masuda & Nisbett, 2001). The holistic pattern of attention was also found among other non-Westem populations such as Russians (Grossmann, 2009;Kiihnen et al, 2001), Central andEastern Europeans (Varnum et al, 2008), and Arabs (Zebian & Denny, 2001). Farming and fishing communities (vs. herding communities; Uskul, Kitayama, & Nisbett, 2008), Orthodox Jews (vs. secular Jews; Vamum et al, 2010), and working-class (vs. middle-class) adults also show a more holistic pattern of attention.…”
Section: The Formation Of Attitudesmentioning
confidence: 78%
“…In contrast, Americans' memory for focal objects was independent of the background (Masuda & Nisbett, 2001). The holistic pattern of attention was also found among other non-Westem populations such as Russians (Grossmann, 2009;Kiihnen et al, 2001), Central andEastern Europeans (Varnum et al, 2008), and Arabs (Zebian & Denny, 2001). Farming and fishing communities (vs. herding communities; Uskul, Kitayama, & Nisbett, 2008), Orthodox Jews (vs. secular Jews; Vamum et al, 2010), and working-class (vs. middle-class) adults also show a more holistic pattern of attention.…”
Section: The Formation Of Attitudesmentioning
confidence: 78%
“…Recent work among East Asians (Ji et al 2004) in industrialized societies using the Rod & Frame Test, the Framed Line Test (Kitayama et al 2003), and the Embedded Figures Test again shows Westerners at the field-independent end of the spectrum, compared to field-dependent East Asians, Malays, and Russians (Kuhnen et al 2001). Similarly, Norenzayan et al (2007) found that Canadians showed less field-dependent processing than did Chinese, who in turn were less field-dependent than were Arabs (also see Zebian & Denny 2001). East Asians' recall for objects is worse than Americans' if the background has been switched (Masuda & Nisbett 2001), indicating that East Asians are attending more to the field.…”
Section: Contrast 2: Western 7 Versus Non-western Societiesmentioning
confidence: 96%
“…Recent work among East Asians (Ji et al 2004) in industrialized societies using the Rod & Frame Test, the Framed Line Test (Kitayama et al 2003), and the Embedded Figures Test again shows Westerners at the field-independent end of the spectrum, compared to field-dependent East Asians, Malays, and Russians (Kuhnen et al 2001). Similarly, Norenzayan et al (2007) found that Canadians showed less field-dependent processing than did Chinese, who in turn were less field-dependent than were Arabs (also see Zebian & Denny 2001).…”
Section: Analytic Versus Holistic Reasoningmentioning
confidence: 91%